Mixed-valence gold bis(diselenolene) complex turning metallic under pressure. Issue 36 (16th August 2021) - Le Gal, Yann; Cui, HengBo; Alemany, Pere; Canadell, Enric; Kato, Reizo; Roisnel, Thierry; Dorcet, Vincent; Fourmigué, Marc; Lorcy, Dominique
Abstract : A rare mixed-valence gold bis(diselenolene) complex, exhibiting charge order between cis and trans isomers stabilized by C–H⋯S interactions, turns metallic under high pressure (>10 GPa) Abstract : While oxidation of d 8 anionic gold bis(dithiolene) complexes most often affords the corresponding neutral radical single-component conductor, an original gold bis(diselenolene) complex isolated as a Ph4 P + salt affords upon electrocrystallization a mixed-valence 1 : 2 salt, [Ph4 P][Au(Me-thiazds)2 ]2 (Me-thiazds: 2-methyl-1, 3-thiazoline-2-thione-4, 5-diselenolate). This salt exhibits a rare charge alternation associated with the simultaneous presence of both cis and trans isomers of the gold complex in the conducting layers. The salt is semiconducting ( σ RT = 3 × 10 −2 S cm −1, E act = 0.137 eV) but, in contrast with other 1 : 2 gold bis(dithiolene) salts, turns metallic under pressure (>10 GPa). [Ph4 P][Au(Me-thiazds)2 ]2 is thus the first metallic, fully characterized, 1 : 2 mixed-valence gold complex, opening the door for the preparation of highly conducting solids of this type.